2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346116
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics measures applied to EEG recordings of patients with Attention Deficit/Hyperactivity Disorder: Quantifying the effects of a neurofeedback treatment

Abstract: This work presents the application of nonlinear dynamics measures to electroencephalograms (EEG) acquired from patients with Attention Deficit/Hyperactivity Disorder (ADHD) before and after a neurofeedback therapy, with the aim to assess the effects of the neurofeedback in a quantitative way. The database contains EEG registers of seven patients acquired in eyes-closed and eyes-opened conditions, in pre-and post-treatment phases. Five measures were applied: largest Lyapunov exponent, Lempel-Ziv complexity, Hur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
11
0
3
Order By: Relevance
“…The degree of complexity is associated with the number of brain connections; decreased connectivity indicates lower complexity, and increased connectivity reflects greater complexity. Numerous studies on brain activity in ADHD have been performed using functional neuroimaging techniques other than fMRI, such as electroencephalography and magnetoencephalography [ 32 , 33 ]. Gómez et al [ 32 ] demonstrated that MEG recordings of ADHD patients were more-regular compared to recordings obtained in a control group; furthermore, there were significant differences among these groups in five brain regions, that is, anterior, central, posterior, left lateral, and right lateral areas.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of complexity is associated with the number of brain connections; decreased connectivity indicates lower complexity, and increased connectivity reflects greater complexity. Numerous studies on brain activity in ADHD have been performed using functional neuroimaging techniques other than fMRI, such as electroencephalography and magnetoencephalography [ 32 , 33 ]. Gómez et al [ 32 ] demonstrated that MEG recordings of ADHD patients were more-regular compared to recordings obtained in a control group; furthermore, there were significant differences among these groups in five brain regions, that is, anterior, central, posterior, left lateral, and right lateral areas.…”
Section: Discussionmentioning
confidence: 99%
“…En otro estudio se encontró la aplicación no lineal de medidas dinámicas del EEG realizada en sesiones pre y post a pacientes con Trastorno por Déficit de Atención con Hiperac tividad (TDAH) (Cerquera, Arns, Buitrago, Gutiérrez & Freund, 2012). Uno de los objetivos de este estudio colombiano es revisar la efectividad de cinco medidas basadas en técnicas de dinámica no lineal, para detectar diferencias en los registros de EEG de pacientes con TDAH antes y después de la terapia de neurofeedback.…”
Section: Ondas Cerebralesunclassified
“…En sus conclusiones los autores plantean que entre los 26 canales de respuesta que generalmente posee un registro EEG, el tres es el más representativo, teniendo en cuenta que esta interpretación cambiará en la medida en que se establezca un objetivo de evaluación particular (Cerquera et al, 2012).…”
Section: Ondas Cerebralesunclassified
“…Both SI and LZC have been employed in several studies aiming to characterize neurological states using EEG signals. 8,[14][15][16][17][18][19][20][21][22][23][24][25][26] Nevertheless, a key issue in the application of these and other nonlinear measures is their sensitivity to nonstationarities in the time series, which is characterized by variations over time of their statistical properties. 27 In case of EEG signals, nonstationarity episodes could be caused mainly by the sensitivity of dynamical parameters to the different time scales in brain activity, 28,29 most likely reflecting dynamical nonstationarity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies employing SI and LZC are available in the current literature, where authors have assumed durations of epochs to fulfil quasistationarity requirements covering values between 1 and 300 seconds. 13,[15][16][17][18][19][20][21][22][23][24]26,[39][40][41][42][43][44][45][46][47] In addition to the search of quasi-stationarity conditions, the number of data points also affects the nonlinear deterministic dynamics of these epochs; this is proportional to the sampling rate utilized in the acquisition of the signal, and too short data sets imply errors in the calculation of nonlinear metrics. Although under certain conditions this length should be larger than 100 000 data points according to criterion proposed by Eckmann and Ruelle 48 for generic time series, Gallez and Babloyantz 49 established that data sets larger than 20 000 data points can be suitable for evaluation of Lyapunov exponents in alpha activity, which is a nonlinear measure that quantifies the chaoticity in a time series.…”
Section: Introductionmentioning
confidence: 99%